ANALISIS KOMPARASI PROSEDUR KEPABEANAN BARANG PENUMPANG DI NEGARA INDONESIA, TIONGKOK, INDIA DAN JEPANG - Nurcahyo, Marsanto Adi; Muslim, Hafizh Adam (Unit Penerbitan Politeknik Keuangan Negara STAN, 2024)
The passenger goods service activities conducted by customs authorities play a significant role in economic growth, the smooth flow of passengers, and international relations among countries. This research aims to elucidate the mechanism of passenger goods import customs procedures in Indonesia, China, Japan, and India. Furthermore, it seeks to discern the disparities in passenger goods import procedures among these countries. The research methodology employed is descriptive qualitative. Data collection methods include literature review and questionnaire dissemination. The findings reveal both similarities and differences in passenger goods import service procedures. The commonality across respondent countries lies in providing customs duty exemption facilities up to a certain value, specific goods carrying facilities, and procedural protocols. Discrepancies in customs procedures arise in the magnitude and quantity of facilities provided for specific goods carriage. Consequently, this research recommends that governments periodically evaluate and adjust the provision of facilities for passenger goods. Additionally, governments can collaborate with relevant countries to harmonize customs procedures.